2021
DOI: 10.3389/fpsyg.2021.570547
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Conceptualization of Filial Piety in the Global Context: From Skin to Skeleton

Abstract: Social science researchers often define filial piety as a set of norms, values, and practices regarding how children should behave toward their parents. In this article, we trace the conceptual development of filial piety research in Chinese and other societies to highlight the assumptions underlying this traditional approach to filial piety research. We identify the limitations of these assumptions, including the problem of an evolving definition and lack of cross-cultural applicability. We then advocate an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 90 publications
(147 reference statements)
4
73
0
1
Order By: Relevance
“…Extant literature on filial piety focused on its influences on care giving behavior and aging policy in Confucian-influenced countries, but neglected its role in influencing individuals' psycho-social functioning (Chen et al, 2016;Bedford and Yeh, 2020). Recently some researchers called for expanding the scope of filial piety studies, both in the research fields and in applications in other cultural backgrounds (Tan et al, 2019;Zhou et al, 2020;Bedford and Yeh, 2021). Yeh and Bedford (2003) have proposed a revised dual filial piety model (DFPM), shifting the focus of conceptualization of filial piety from cultural norms to the inherent structure of the relationship between parents and children.…”
Section: Introductionmentioning
confidence: 99%
“…Extant literature on filial piety focused on its influences on care giving behavior and aging policy in Confucian-influenced countries, but neglected its role in influencing individuals' psycho-social functioning (Chen et al, 2016;Bedford and Yeh, 2020). Recently some researchers called for expanding the scope of filial piety studies, both in the research fields and in applications in other cultural backgrounds (Tan et al, 2019;Zhou et al, 2020;Bedford and Yeh, 2021). Yeh and Bedford (2003) have proposed a revised dual filial piety model (DFPM), shifting the focus of conceptualization of filial piety from cultural norms to the inherent structure of the relationship between parents and children.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional views of filial beliefs ( filial piety ) refer to the attitudes of children toward how they should treat their parents, as well as an emphasis on respect and care for elders, containing important ideas about social relations (Ho, 1986 ; Yeh, 2003 ). In modern psychological studies, we can observe the evolution of the conceptualization of filial piety: initially treated as a Chinese value-based cultural norm; nowadays, filial piety is viewed as universal construct, defined as a cognitive script or even a contextualized personality construct for social exchanges (Bedford and Yeh, 2019 , 2021 ). Having considered the foregoing, the concept of filial piety was transferred from the cultural dimension ( emic ) to the personality dimension ( etic ), demonstrating the universal mechanism of child-parent relationships found in diverse cultures, such as Korea, Japan, Malaysia, Thailand, Vietnam, USA, and even Poland.…”
Section: Introductionmentioning
confidence: 99%
“…However, research has found that, explicitly, this was the case but, implicitly, filial piety was changing in a modern direction, affected by modern individualistic western-influenced cultural ideas (Zhang et al, 2021). Bedford and Yeh (2021) discussed the evolution of the conceptualization of filial piety and developed the Dual Filial Piety Model. This model suggests two kinds of filial piety: reciprocal and authoritarian (Yeh, 1997;Bedford and Yeh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bedford and Yeh (2021) discussed the evolution of the conceptualization of filial piety and developed the Dual Filial Piety Model. This model suggests two kinds of filial piety: reciprocal and authoritarian (Yeh, 1997;Bedford and Yeh, 2021). Reciprocal filial piety is defined as affection-based gratitude and respect for parents' efforts, while authoritarian filial piety refers to the relationship hierarchies and role obligations that demand children's compliance with their parents (Yeh and Bedford, 2003;Bedford and Yeh, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation